Walking as an approach to the socially-ecological transformation of inclusive urban mobility systems: An explorative case study involving disabled people in Berlin - Julian Horn (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2024)
The worsening climate crisis calls for restructuring mobility systems and urban infrastructure. One goal of the socio-ecological transformation in the mobility sector is to promote walking. Measurements of pedestrian friendliness are summarised under the term walkability or walkability index, but they mostly lack the perspectives of people with disabilities. To address this gap, five mobile interviews with disabled people in Berlin were conducted to identify specific barriers, perceived safety risks, and well-being, which have remained unconsidered in recent measurements. Curb ramps, ground conditions, tacticle walking surface indicators, parking cars, other road users, and noise were the most important factors that should be integrated into further concepts of walkability indices. The study also shows how disabled people are discriminated against by urban infrastructure and how this affects their mobility and well-being.
Keywords: 300; Walkability; Walkability Indices; Inclusion; Mobility of disabled people; Barriers; Urban Infrastructure